Reading sixteenth-century poetry - Cheney, Patrick, 1949-; Wiley InterScience (Online service) (Malden, MA : Wiley-Blackwell, 2011)
Reading Sixteenth-Century Poetry combines close readings of individual poems with a critical consideration of the historical context in which they were written. Informative and original, this book has been carefully designed to enable readers to understand, enjoy, and be inspired by sixteenth-century poetry. Close reading of a wide variety of sixteenth-century poems, canonical and non-canonical, by men and by women, from print and manuscript culture, across the major literary modes and genresPoems read within their historical context, with reference to five major cultural revolutions: Renaissan.
The pleasures and uses of sixteenth-century poetry -- pt. 1. 1500-1558. Reading early Tudor poetry: Henrician, Edwardian, Marian -- pt. 2. 1558-1600: reading Elizabethan poetry -- pt. 3. A special case -- Retrospective poetry: Donne and the end of sixteenth-century poetry.
Includes bibliographical references and index.
Print version record.
Keywords: 1500-1599; English poetry -- 16th century -- History and criticism; English poetry -- Appreciation; LITERARY CRITICISM -- Shakespeare; English poetry; English poetry -- Appreciation; Intellectual life; England -- Intellectual life -- 16th century; England; Electronic books; Criticism, interpretation, etc